The Doctrine of Provocation Defence and a Murder Based on Jealousy - Slavković, Vukian (Teisė, 2023)
The paper presents the essential characteristics of the qualification of murder motivated by a jealousy in modern comparative legislation. Since this topic causes special attention of legal theory, the author has conducted research which has shown that three approaches represent different doctrinal opinions.